2017
DOI: 10.1007/s12192-016-0746-9
|View full text |Cite
|
Sign up to set email alerts
|

Putative model for heat shock protein 70 complexation with receptor of advanced glycation end products through fluorescence proximity assays and normal mode analyses

Abstract: Extracellular heat shock protein 70 (HSP70) is recognized by receptors on the plasma membrane, such as Tolllike receptor 4 (TLR4), TLR2, CD14, and CD40. This leads to activation of nuclear factor-kappa B (NF-κB), release of proinflammatory cytokines, enhancement of the phagocytic activity of innate immune cells, and stimulation of antigenspecific responses. However, the specific characteristics of HSP70 binding are still unknown, and all HSP70 receptors have not yet been described. Putative models for HSP70 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…In this study, we used a human lung cancer-derived A549 cell line, which constitutively expresses RAGE, and validated the interaction between this receptor and eHSP70 by a cellular study-based approach. Since the interaction between eHSP70 and RAGE has already been reported [23, 24], our immunoprecipitation and protein proximity image assay results confirmed this specific binding around the cell, leading us to use this cell model to investigate functional signaling responses evoked by eHSP70-RAGE engagement. It is important to note that the evaluation of functional responses mediated by RAGE is a major step to establish eHSP70 as a RAGE agonist, since HSP70 is able to interact with a myriad of proteins due to its chaperone activity.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, we used a human lung cancer-derived A549 cell line, which constitutively expresses RAGE, and validated the interaction between this receptor and eHSP70 by a cellular study-based approach. Since the interaction between eHSP70 and RAGE has already been reported [23, 24], our immunoprecipitation and protein proximity image assay results confirmed this specific binding around the cell, leading us to use this cell model to investigate functional signaling responses evoked by eHSP70-RAGE engagement. It is important to note that the evaluation of functional responses mediated by RAGE is a major step to establish eHSP70 as a RAGE agonist, since HSP70 is able to interact with a myriad of proteins due to its chaperone activity.…”
Section: Discussionsupporting
confidence: 75%
“…TLR, CD14) are strongly influenced by RAGE, such as ERK1/2-mediated activation of NF-kB. Furthermore, an ELISA screen assay proposed a potential interaction between RAGE and extracellular HSP70 [23], while a recent work by our group proposed an interaction model by molecular docking and evidenced a physical interaction between RAGE-eHSP70[24]. However, since the activity of HSP70 as molecular chaperone allows nonspecific interactions with diverse proteins, the aim of the current study was to investigate if the eHSP70-RAGE interaction is able to induce a functional activation of RAGE in a cellular model, in order to establish eHSP70 as a functional RAGE agonist.…”
Section: Introductionmentioning
confidence: 99%
“…The utmost goal in molecular docking is to use algorithms to predict the likelihood that a given protein will bind to a target. Here, we identified the same pattern observed by Grunwald and collaborators [32] where the ATP-bound state of HSP70 formed a more stable interaction with the TLR4/MD2 complex (Table 2) with no significant deformability in the interface (Figure 4). This might be because the two domains of HSP70 in the ADP-bound state could rotate in opposite directions, making the protein a not very likely ligand, at least in this conformation, which was not observed in the ATP-bound state [32].…”
Section: Discussionsupporting
confidence: 88%
“…In a previous study, aiming at elucidating the complexation model between HSP70 and the receptor for advanced glycation end product [RAGE (IDs 3CJJ and 4LP5)], the authors showed that the ADP bound state (ID 2KHO) also formed a complex with the receptor although it was less energetically favorable [32]. In our molecular docking simulations, we aimed at characterizing HSP70 affinity towards the human TLR4/MD2 (ID 3FXI) complex using both ADP (ID 2KHO) and ATP (ID 4B9Q) states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation